Three‐dimensional and two‐and‐a‐half‐dimensional face recognition spoofing using three‐dimensional printed models. Issue 2 (1st June 2016) - Galbally, Javier; Satta, Riccardo
Abstract : The vulnerability of biometric systems to external attacks using a physical artefact in order to impersonate the legitimate user has become a major concern over the last decade. Such a threat, commonly known as 'spoofing', poses a serious risk to the integrity of biometric systems. The usual low‐complexity and low‐cost characteristics of these attacks make them accessible to the general public, rendering each user a potential intruder. The present study addresses the spoofing issue analysing the feasibility to perform low‐cost attacks with self‐manufactured three‐dimensional (3D) printed models to 2.5D and 3D face recognition systems. A new database with 2D, 2.5D and 3D real and fake data from 26 subjects was acquired for the experiments. Results showed the high vulnerability of the three tested systems, including a commercial solution, to the attacks.